2018
DOI: 10.1038/s41467-018-04975-2
|View full text |Cite
|
Sign up to set email alerts
|

Vapor sublimation and deposition to build porous particles and composites

Abstract: The vapor deposition of polymers on regular stationary substrates is widely known to form uniform thin films. Here we report porous polymer particles with sizes controllable down to the nanometer scale can be produced using a fabrication process based on chemical vapor deposition (CVD) on a dynamic substrate, i.e., sublimating ice particles. The results indicate that the vapor deposition of a polymer is directed by the sublimation process; instead of forming a thin film polymer, the deposited polymers replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…The bacteria-encapsulated capsule was fabricated by first preparing ice templates by directly transforming the liquid-phased bacteria-cultured media into a solidified ice template in a liquid nitrogen-conditioned bath. Subsequently, the fabrication exploited the previously described sublimation of ice and deposition of poly- p -xylylene in one continuous step [ 16 , 17 ] to construct a bacterially encapsulated polymeric capsule. A second transformation was performed with vapor-deposited poly- p -xylylene molecules to replace the resulting space when the sublimated ice/water molecules evaporated from the ice templates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteria-encapsulated capsule was fabricated by first preparing ice templates by directly transforming the liquid-phased bacteria-cultured media into a solidified ice template in a liquid nitrogen-conditioned bath. Subsequently, the fabrication exploited the previously described sublimation of ice and deposition of poly- p -xylylene in one continuous step [ 16 , 17 ] to construct a bacterially encapsulated polymeric capsule. A second transformation was performed with vapor-deposited poly- p -xylylene molecules to replace the resulting space when the sublimated ice/water molecules evaporated from the ice templates.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, transformation of the template resulted in the construction of composite materials with defined physical properties in terms of porosity, bulk size and geometry, and chemical functionality by the compartmentalized functional entities and the devised interfacial chemistries [ 16 ]. With respect to the vapor sublimation and deposition process, which has been reported to result in the precise localization and distribution of substances such as metals, molecules, and liquids to form composites with controlled homogeneity or anisotropy from various materials [ 15 , 17 ], we hypothesized that the benign and versatile vapor-phased process was able to encapsulate (i) unmodified native bacteria of the Bacillus species CMC1 (hereafter referred to as B. CMC1 ) with specific enzymatic function and the same precision to localize and distribute B. CMC1 due to the encapsulation technique, enabling well-controlled bacterial growth activities and functions, and (ii) a regulator molecule, carboxymethyl cellulose (CMC), with a customizable encapsulation concentration to provide the same customizable stimulation dosages to regulate the enzymatic functions of the neighboring B. CMC1 bacteria. The fabricated and encapsulated capsules were composed of inhabitant bacteria from (i) and the surrounding conditioning regulator molecules from (ii), and the synergistic activities exhibited by (i) and (ii) were able to deliver a combination of controlled enzymatic factors for bioremediation in the devised microenvironments ( Figure 1 a).…”
Section: Introductionmentioning
confidence: 99%
“…We therefore introduced a vapor-based synthesis of a porous material that comprised poly- p -xylylene as the backbone matrix and was equipped with methyl propiolate functionality to perform a metal-free 1,3-dipolar cycloaddition click reaction from the interface. The construction of the porous material is based on our previous discovery that the deposition of poly- p -xylylene on sublimated ice templates (instead of non-sublimated substrates) can result in the production of a three-dimensional and porous poly- p -xylylene material [ 18 ], and the shape, size, and inner porous structure of the porous polymer products are also customizable [ 19 , 20 ]. It has also been reported that the deposition of poly- p -xylylenes can be functionalized by using substituted [2,2]-paracyclophanes as the precursors during the chemical vapor deposition (CVD) polymerization process [ 21 ], and a variety of functional groups, such as amine, hydroxyl, vinyl, alkyne, maleimide, aldehyde, and disulfide groups, which were successfully produced to form functionalized poly- p -xylylene coatings and performed tasks for biointerface engineering [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, many schemes have been proposed, among which the direct manipulating and positioning of the right atoms and molecules in the right place is the most attractive one. This can be divided into two categories: one is to manipulate the atom and molecule one by one (representing point-by-point manipulation), such as STM technology [12,13,14,15,16,17,18,19,20,21,22,23]; the other is to manipulate hundreds of millions of atoms and molecules (clusters) simultaneously (representing macroscopic manipulation), such as magnetron sputtering [24,25], molecular beam epitaxy [26,27], evaporation plating [28], sublimation [29], etc. Obviously, the former can manipulate atoms and molecules precisely to the designed places to manufacture objects [12,13,14,15,16,17,18,19,20,21,22,23]; however, this is practically difficult for large-sized objects [30].…”
Section: Introductionmentioning
confidence: 99%